Technical note: Evolution of convective boundary layer height estimated by Ka-band continuous millimeter wave radar at Wuhan in central China - Z. Zhang; Z. Zhang; Z. Zhang; K. Huang; K. Huang; K. Huang; F. Yi; F. Yi; F. Yi; W. Cheng; F. Liu; F. Liu; et al. (Atmospheric Chemistry and Physics)
Using the vertical velocity (w) observed by a Ka-band millimeter wave cloud radar (MMCR) at Wuhan, we investigate the evolution of the convective boundary layer height (CBLH) based on a specified threshold of vertical velocity variance (<msubsup>σw2</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="9b56224698e9b9cd666fa4380cc7c0dd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-3347-2025-ie00001.svg" width="14pt" height="16pt" src="acp-25-3347-2025-ie00001.png"/></svg:svg>). The CBLHs from the MMCR w in the selected durations are compared with those estimated by the lidar range-corrected signal (RCS) and radiosonde temperature based on different algorithms, showing good agreement with each other. Although these algorithms are based on different dynamic and thermodynamic effects, the diurnal evolution of the CBLH from MMCR is generally consistent with that from lidar, except for a few hours post-sunrise and pre-sunset due to the influence of the aerosol residual layer on the lidar RCS. Meanwhile, the CBLH from MMCR shows less variation with the occurrence of sand and dust and a swifter response for thick clouds relative to that from lidar. In this case, <msubsup>σw2</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="14pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="2a1698782d2a3a0cd31bf65df271295b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-3347-2025-ie00002.svg" width="14pt" height="16pt" src="acp-25-3347-2025-ie00002.png"/></svg:svg> of the MMCR w identifies the CBLH based on a dynamic effect, which can accurately capture the diurnal evolution of the CBLH compared with that from the change in long-time-mixing aerosol concentration. The monthly and seasonal features of the CBLH at Wuhan are revealed via the MMCR measurement. Hence, considering that the MMCR is capable of continuous observation in various weather conditions, the MMCR w with high resolution can be applied for monitoring the evolution of the CBLH in different atmospheric conditions, which is helpful for improving our comprehensive understanding of the convective boundary layer (CBL) and dynamic processes in the CBL.